Hardware Implementation of Single Phase Power Factor Correction System using Micro-controller - Kartikesh Kumar Jha; Bidyut Mahato; Prem Prakash; Kartick Chandra Jana (Institute of Advanced Engineering and Science, 2016)
Rapid increase of consumers in electronics devices and the use of mains rectification circuits inside these electronic devices is the root cause of mains harmonic distortion. Automatic power factor correction techniques can be applied to the industries, power systems and households to make them stable inturns increases the efficiency of system as well as the apparatus. This paper deals with the hardware design of active power factor correction circuit employing boost converter which is used to boost the DC voltages with a controller based on PID control strategy. The pulses given to power switches by pulse width modulation techniques generated by utilizing micro-controller board, Arduino thus obviating the need of complex hardware circuitry. MATLAB/SIMULINK was used to design and tune the PID controller parameters. The simulation results are matching with the predictions and the same was implemented as hardware. The waveforms various test points and across capacitors were obtained, studied and compared with the theoretical waveforms and are found to be in precise proximity of theoretical waveforms.